2015
DOI: 10.1097/maj.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rheumatoid Arthritis Patients’ Adherence to Treatment

Abstract: Background: Reports on adherence among patients with rheumatoid arthritis (RA) in Egypt and the Middle East region are lacking. This study aimed to measure adherence to treatment among a sample of patients with RA at Ain Shams University Rheumatology outpatient clinic and to assess factors affecting it. Methods: A crosssectional descriptive study was carried out at the rheumatology outpatient clinic on a sample of 140 patients with RA. An interview questionnaire was used to measure adherence using the 8-item M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 27 publications
4
41
2
4
Order By: Relevance
“…Importantly, the markers with strongest influence were those associated with MMP-driven bone (ICTP) and connective tissue (C1M) remodelling. References: [1] Smolen JS.Tocilizumab inhibits progression of joint damage in rheumatoid arthritis irrespective of its anti-inflammatory effects: disassociation of the link between inflammation and destruction. Ann Rheum Dis 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the markers with strongest influence were those associated with MMP-driven bone (ICTP) and connective tissue (C1M) remodelling. References: [1] Smolen JS.Tocilizumab inhibits progression of joint damage in rheumatoid arthritis irrespective of its anti-inflammatory effects: disassociation of the link between inflammation and destruction. Ann Rheum Dis 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Objectives: Serological markers together with clinical parameters was tested in a multi-marker model to assess its ability to objectively predict progression of RA. Methods: Current post-hoc analysis included RA patients from the biomarker substudy of the phase III clinical study LITHE investigating the safety and efficacy of tocilizumab [1][2][3][4] . Patients had moderate/severe, active RA.…”
Section: Scientific Abstractsmentioning
confidence: 99%
“…Other eight articles in the same category (61.5%) analyzed the consequences of patients' beliefs about drugs on adherence. Although most patients with RA believed their synthetic and biological DMARDS were necessary to preserve joint structures, reduce pain and increase quality of life, levels of concern about side effects were high and related to non-adherence [3,5,15,16,[41][42][43][44]. Beliefs about cause of disease expressed by RA patients in 9 studies (12.1% of articles reporting beliefs) included: hereditarity, stress, unexpressed grief, diet, occupational factors/overwork, lack of exercise, God's will, weather conditions, biological reasons/immune system failure/autoimmunity, accident/chance and karmic explanation (disease caused by past "bad" actions) [18,36,43,[45][46][47][48][49][50].…”
Section: Beliefs About Pharmacological and Non-pharmacological Therapmentioning
confidence: 99%
“…The identification of the diagnostic and/or prognostic value of such novel auto-Abs is under intense investigation. We recently demonstrated that RA patients display a higher prevalence of auto-Abs against the interferon-inducible protein 16 (anti-IFI16) but these auto-Abs do not have a good diagnostic value (1). Recent data showed that auto-Abs against citrullinated alpha-enolase (anti-CEP1) are associated with erosive RA (2).…”
mentioning
confidence: 99%
“…Auto-Abs were assessed as follows: anti-CCP EDIA 2nd generation ELISA kit (Eurodiagnostica); anti-CEP-1 IgG ELISA kit (Euroimmun). In a subgroup of 113 patients also anti-IFI16 auto-Abs were assessed with an in-house ELISA kit (1). Clinical and serological records of patients were collected and statistical analysis was performed with SPSS 21.0 software.…”
mentioning
confidence: 99%